Quantitatively evaluating activity and number of catalytic sites on metal oxide for ammonium perchlorate decomposition. Issue 5 (20th January 2022) - Zhou, Lin‐Yu; Cao, Shao‐Bo; Zhang, Liang‐Liang; Xiang, Guolei; Zeng, Xiao‐Fei; Chu, Guang‐Wen; Chen, Jian‐Feng
Abstract: Ammonium perchlorate (AP) catalytic thermal decomposition by metal oxides is complex and there is still no suitable quantitative evaluation method to characterize intrinsic catalytic activity. Here, a new method to quantitatively evaluate the catalytic capability of metal oxides for AP decomposition has been proposed. We introduce two indicators, intrinsic peak temperature ( T HTD * ) and catalytic density ( ρ T * ) in high‐temperature decomposition process, to uncouple activity and number of catalyst sites. Hematite (α‐Fe2 O3 ) nanostructures with different shapes have been used as model catalysts to verify the feasibility of this method. Rod‐like α‐Fe2 O3 shows the best catalytic performance in AP decomposition with the lowest T HTD * of 345.1°C and highest ρ T * of 0.544, which indicate the largest number and highest activity of catalytic sites. Moreover, these new indicators are theoretically proven to be reasonable by density functional theory calculations.